Two-dimensional DOA estimation algorithm with co-prime array via sparse representation - Cheng, Zengfei; Zhao, Yongbo; Li, Hui; Shui, Penglang (Electronics letters, 2015)
A two-dimensional (2D) direction-of-arrival estimation algorithm is proposed with the co-prime array based on the sparse representation framework. By constructing a cross-correlation matrix of the received signals, the array aperture is extended and the 2D angle information is separated into two independent parts. Then, a procedure of sparse signal representation and least square are used to estimate and pair the 2D angles successively and automatically. Without the prior knowledge of the signal number, the proposed algorithm provides more precise angle estimation. Simulation experiments verify the effectiveness of the proposed algorithm.